Clinical Evaluation of Dibekacin in Urinary Tract Infection in Children - Taralan Tambunan; I. G. N. Wila Wirya; Husein Alatas (Paediatrica Indonesiana, 1982)
Fifty selected cuses of urinary tract infection ( UTI) were treated with Dibekacinwith the do~age of 2 mg/kg BW, IM. for seren days. Thirty five casesclassified as simple UT 1 and /lie rest fifteen cases as complicured urinary infection. Thirty one cases were injected once a day and the remaining nineteen patients twice a day.The .ciinica!, laboratory und microbiological improvement was 84%, 86%and 62% respectively. Complete improvement was and on 54% cases only. Inthe group of simple UTI, no significant different result was found on differentinterval time of drug injection. Similar result was also detected in the group ofcomplicated UTI. The only significant different result was obtained from thecumparison between simple and complicated urinmy infection when the drugwas given twice a day, either it was separately assessed clinically, latoratoryand microbiologically or combined. Better result was more pronounced in thegroup of simple UTI but we had to be cautious to interpret this finding. Singledaily injection could be reconunended to reduce the dscomfort of parenteraladministration.